Problematic issues of agricultural waste processing in Ukraine and ways to solve them according to European trends in the framework of the circular economy - Smirnova, Angelina; Yastremska, Larysa; Korniienko, Iryna; Kuznietsova, Olena; Baranovskyy, Mikhaylo (Problems of Environmental Biotechnology, 2024)
The problematic issues of agricultural waste processing in Ukraine and ways to solve them according to European trends in the framework of the circular economy are highlighted